A Synthesis of Alsmaphorazine B Demonstrates the Chemical Feasibility of a New Biogenetic Hypothesis - Hong, Allen Y.; Vanderwal, Christopher D. (Journal of the American Chemical Society, 2015)
An N-oxide fragmentation/hydroxylamine oxidation/intramolecular 1,3-dipolar cycloaddition. Cascade, efficiently converted an oxidized congener of akuammicine into the complex, hexacyclic architecture of the alsmaphorazine alkaloids. This dramatic structural Change shows the chemical feasibility of our novel proposal for alsmaphorazine biogenesis, Critical to these endeavors was a marked improvement in our previously reported Zincke aldehyde cycloaddition approach to indole alkaloids, which permitted the gram--scale synthesis of akuammicine. The chemoselective oxidations of akuammicine leading tip to the key rearrangement also generated several biogenetically related alkaloids of the alstolucine and alpneumine families.